Inland Waterways Infrastructure - Victoria, Ong Argo (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
Inland Waterways infrastructure is usually in the form of natural infrastructure in the form of rivers that can be used for cheap transportation, but sometimes problems are found in order to optimize their use by constructing canals, transfer ponds or have to be regularly treated and dredged especially on rivers that flow the rivers are out of control so that erosion that occurs in the river flow area in turn results in shallowing of the shipping lanes.